Martius Flap Technique for Repairing Rectovaginal Fistulas: A Comprehensive Review with Emphasis on Gynecological Etiologies - Al-Kubati WR (Open Access Surgery, 2024)
Waheeb Radman Al-Kubati1,2 1Surgery Department, 21st September University, Sana’a, Yemen; 2Physiology Department, Sana’a University, Sana’a, YemenCorrespondence: Waheeb Radman Al-Kubati, Surgery Department, 21st September University, Sana’a, Yemen, Email waheebradman@yahoo.comBackground: Rectovaginal fistulas (RVFs) present a significant surgical challenge, particularly those resulting from gynecologic procedures, which are often complex and associated with higher recurrence rates. The Martius Flap technique, which involves the use of a vascularized adipose tissue graft, is an established method for enhancing fistula repair, especially in cases involving large, recurrent, or radiation-induced fistulas.Materials and Methods: We conducted a prospective evaluation of 46 female patients with RVFs treated using the Martius Flap technique between December 2008 and December 2019. The study focused on patients with RVFs caused predominantly by gynecologic procedures, including surgeries for benign and malignant conditions, as well as those with a history of radiation therapy.Results: The average age of the patients was 38.7 years (range 18– 75 years). Of the 46 RVFs treated, 65.2% were due to gynecologic surgery, 26.1% were associated with iatrogenic injury or radiation therapy, and 8.7% were post-coital. Successful fistula closure was achieved in 95.6% of cases, with a recurrence rate of 4.4%. The Martius Flap demonstrated high efficacy, particularly in large and complex fistulas, with most patients reporting significant satisfaction and improved continence post-operatively.Conclusion: The Martius Flap technique is a highly effective option for the surgical management of RVFs, particularly those secondary to gynecologic procedures. The technique’s ability to introduce well-vascularized tissue into the repair site significantly reduces recurrence rates and enhances healing, making it a preferred method for treating complex and recurrent RVFs.Keywords: Martius flap, rectovaginal fistula, RVF, transperineal approach, surgical repair, complications